Capital Investment and Profitability Across Malaysian Construction Sectors - Qi Yang, Lim; Ramakrishnan, Suresh; Mohd Jamal, Noriza; Mohamed Saat, Maisarah; Faizan Malik, Muhammad (International Journal of Engineering and Technology, 2018)
Capital investment and profitability are the most important factors in every firms. Capital investment will determine profitability of the firm by having efficient and effective investment portfolio to the firm. This study investigates the relationship of capital investment and profitability among Malaysia listed construction firms from 2001-2014. Furthermore, this study also analyzes the impact of capital investment on profitability in different economic sub-periods. In addition, this study also used Pooled OLS analysis and fixed effect analysis to analyze and determine the relationship between dependent and independent variables. I.e.: capital investment such as investment to asset, capital expenditure and current capital expenditure along with profitability such as return on asset and return on equity as well as the control variables namely firm size and leverage. The overall results revealed that capital expenditure have significant relationship with return on asset and return on equity. On the other hand, the relationship between capital investment and profitability are differ across different economic sub-periods will produce different outcome. Investment to asset had significant impact towards return on asset and return on equity during pre-crisis period and post-crisis period but during Global Financial Crisis period current capital expenditure has the largest impact towards profitability of the firm. Â Â